Pengaruh Kapasitas Individu dan Asimetri Informasi pada Senjangan Anggaran dengan Budaya Organisasi Sebagai Pemoderasi - Guntur, Ida Bagus Putu Satriya Wibawa; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi; Vol 27 No 1 (2019)DO - 10.24843/EJA.2019.v27.i01.p02, 2019)
This research was conducted at the Head Office of the Regional Development Bank of Bali. The number of samples obtained was 158 observations. Based on the results of the study, it is known that organizational culture is able to moderate the influence of individual capacity on budgetary slack and information asymmetry on budgetary slack. The application of good organizational culture (tri hita karana) to all employees in carrying out their obligations is able to minimize the occurrence of opportunistic actions, namely budgetary slack. The theoretical implications of the research are in addition to references to further research regarding research relating to attribution theory and agency theory. On the other hand the practical implications of research are to provide various considerations to the company in order to be able to minimize the occurrence of budgetary slack. Keywords: Individual capacity, information asymmetry, budgetary slack and organizational culture